UNDERSTANDING SOCIAL MEDIA MARKETING: CONSEQUENCES ON CONSUMER ENGAGEMENT AND REPURCHASE INTENTION AMONG SMEs IN INDONESIA - Negara, Wana Pramudyawardana Kusuma; Nugroho, Sahid Susilo (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study examines the influence of social media marketing activities (entertainment, customization, interaction, and trendy content) on consumer engagement and repurchase intention in the context of Indonesian Small and Medium Enterprises (SMEs). Using the COBRAs (Consumers"™ Online Brand-Related Activities) framework, this research analyzes three levels of engagement: content consumption, content contribution, and content creation. A total of 265 respondents were selected through purposive sampling, and the data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that entertainment and interaction significantly influence all engagement dimensions, while trendy content affects only content consumption. Customization, however, does not significantly impact any engagement level. Additionally, only content consumption and content creation are positively associated with repurchase intention. This study contributes theoretically by extending the application of the COBRAs framework to an emerging market context, addressing limitations in prior studies that primarily focused on Western consumers and large-scale enterprises. The findings offer practical insights for SMEs in developing more targeted social media strategies to strengthen consumer engagement and drive repurchase behavior. JEL: M31, M37.